Study of Z boson plus jets events using variables sensitive to double-parton scattering in pp collisions at 13 TeV; Journal of High Energy Physics; Vol. 2021, iss. 10 - Tumasyan A. R.; Adam W. Wolfgang; Andrejkovic J. W. Aleksandr Dmitrievich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen